Pengaruh Perencanaan Anggaran Dan Penyerapan Anggaran Terhadap Kinerja Instansi Pemerintah - Ajeng Fadhilatunnisa; Sulistia Suwondo; Ira Novianty (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Budget planning and budget absorption are very important to make a good performance of government agencies. Budget planning will determine how and for what budget is absorbed, so that the amount of budget absorption can show how the program is implemented, while the implemented program will show how the performance of a government agency. The aims of this research is to determine the effect of Budget Planning and Budget Absorption either partially or simultaneously to the Performance of Government Agencies. The type of this research is quantitative method. The population are 60 Regional Work Unit (SKPD) Bandung City. The sampling a saturated sample. This research is used primary data. The technique of data analysis is using multiple linear regression. Based on the results of this research, there is a positive influence of budget planning and budget absorption on the performance of government agencies either partially or simultaneously.